Investigating teacher discourse: external aids to internal perspectives - Adriana de Carvalho Kuerten Dellagnelo (Signum: Estudos da Linguagem, 2007)
The present study seeks to investigate the kind of knowledge that most has influenced four teacher-trainees’ teaching. In order to pursue the purpose of this study, representations of reality – with its focus on roles ascribed to trainees and to their students – and social relations – with its focus on the discussion of foreign language teaching principles – are examined in the light of critical discourse analysis (FAIRCLOUGH, 1992) and systemic-functional grammar (HALLIDAY, 1994). The findings obtained in the analysis of ideational and interpersonal meanings indicate that the trainees, to a higher or lesser extent, picture themselves as more powerful and dominant social participants, whose roles are more active and central to the ongoing development of the lessons. When approaching foreign language teaching principles, the trainees present incoherence in reporting to hold beliefs that their discursive practices fail to corroborate. However difficult it may be to draw a clear-cut distinction between theoretical and experiential knowledge, the interpretations raised corroborate the literature in teacher education (BAILEY et al, 1996; FREEMAN, 1996a; FREEMAN, 1996b; FREEMAN; JOHNSON, 1998; FLOWERDEW, 1998) by suggesting that novice teachers tend to be influenced by experiential knowledge to a greater extent, also reiterating the contention that discourse is not only shaped by but also shapes social action (FAIRCLOUGH, 1992).